To die but once [compact disc, unabridged] - Winspear, Jacqueline, 1955- (Winspear, Jacqueline, 1955- Maisie Dobbs novel., 2018)
Spring 1940. Maisie Dobbs is asked to investigate the disappearance of a local lad, a young apprentice craftsman working on a 'hush hush' government contract. As Maisie's inquiry reveals a possible link to the London underworld, another mother is worried about a missing son. But this time the boy in question is one beloved by Maisie.